Die großen Helfer (Arena, 1983)
SCHAGWÖRTER<S>: WWF<S>. Freud<S>. Penn<S>. TerreDesHommes<S>. SOS<S>. SternHelen<S>. MoserS>. Greenpeace<S>. AnonymeAlkoholiker<S>: AmnestyInternational<S>. MutterTeresa<S>. Korczak<S>. Gmeiner<S>. Heuss<S>. Steiger<S>. Pestalozzi<S>. Wilberforce<S>. Sklaven<S>. Cinquin<S>. Koch<S>. Behring<S>. Ehrlich<S>. Raiffeisen<S>. Nansen<S>. Braille<S>. Semmelweis<S>. Brandner<S>. Bodelschwingh<S>. Lebenshilfe<S>